2016
DOI: 10.1111/vde.12393
|View full text |Cite
|
Sign up to set email alerts
|

The novel high molecular weight Dermatophagoides farinae protein Zen‐1 is a major allergen in North American and European mite allergic dogs with atopic dermatitis

Abstract: This study establishes Zen-1 as a major allergen in atopic dogs sensitized to Df.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 27 publications
9
32
0
Order By: Relevance
“…Given that no commercially available Der f 2 test exists, it is important to assess whether Der f 2 immunotherapy may be helpful in the treatment of Df sensitized dogs in the absence of this information. In one study, only 28% of European dogs showed positive IgE serology against Der f 2 . However, another study performed in Portugal and Spain challenged these findings and suggested that Der f 2 reactivity is prevalent, at least in Southern European atopic dogs .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given that no commercially available Der f 2 test exists, it is important to assess whether Der f 2 immunotherapy may be helpful in the treatment of Df sensitized dogs in the absence of this information. In one study, only 28% of European dogs showed positive IgE serology against Der f 2 . However, another study performed in Portugal and Spain challenged these findings and suggested that Der f 2 reactivity is prevalent, at least in Southern European atopic dogs .…”
Section: Discussionmentioning
confidence: 98%
“…Data on the prevalence of Der f 2 sensitization in Europe are conflicting and mainly suggest a low prevalence . Because Allermmune ® has thus far only been tested in Japanese dogs and dogs experimentally sensitized to Der f 2, the goal of this study was to evaluate the short‐term efficacy of Allermmune ® in atopic European dogs showing positive test reactions to Dermatophagoides farinae (Df).…”
Section: Introductionmentioning
confidence: 99%
“…These difering results prompted further European studies and, very recently, the presence of anti-Der f 1, Der f 2, Der f 15 and Der f 18-speciic IgE was detected in the serum of 18 Spanish atopic dogs sensitised to DF, resulting in the revised view that both low and high MW allergens are important in continental Europe. 15 To further concur with the Japanese group's indings, Olivry et al 16 concluded that Zen 1 was also a major allergen in North American and European atopic dogs sensitised to house dust mites. The reasons for the diferences between the various studies over time are unclear and many factors may play a role, not least the diferent methods of allergen/antibody detection and identiication used in the various studies.…”
Section: Introductionmentioning
confidence: 85%
“…This finding may be explained by the fact that there could be different routes of sensitization in atopic dermatitis and respiratory allergy but also by a more polyclonal response in patients with atopic dermatitis which includes otherwise more rarely recognized allergens. Allergic dogs which mainly show atopic dermatitis as the most relevant allergic manifestation also mount IgE-reactivity preferentially to house dust mite body-derived allergens [38] but not to allergens which are associated with airborne feces. This would indicate that the body-derived allergen indeed may sensitize via the skin.…”
Section: Allergen Molecules To Study Atopic Dermatitis Pathomechanismsmentioning
confidence: 99%